Exploring Supply Managers' Intrapreneurial Ability and Relationship Quality. - Steward,Michelle; Wu,Zhaohui; Hartley,Janet (Journal of Business-to-Business Marketing, 2010)
This article examined the degree to which a supply manager's intrapreneurial ability influences the quality of individual-level relationships with internal customers and the supplier's account executive. The moderating influence of the buyer's firm-level commitment to the supplier and how these relationships subsequently impact supplier performance were explored. The study assessed the supply manager's intrapreneurial ability using survey data gathered from 110 supply managers across a variety of industries. In key supplier relationships, a supply manager's intrapreneurial ability positively influences the quality of internal and external relationships. The firm's commitment to the supplier weakens the relationship between intrapreneurial ability and relationship quality. The findings highlight the value of individual skills to enhance relationships The ability to behave intrapreneurially shapes the quality of internal and supplier relationships. However, only the supply manager's relationship with the supplier's account executive is related to supplier performance. By examining the impact of intrapreneurial ability on individual-level relationships with internal customers and supplier's account executive, a more comprehensive view of business-to-business relationship management in the supply chain is gained.
Keywords: Supply Chain